Preparation process of antibacterial acrylic fabric
By introducing modified nanocellulose and silver-carrying carbon balls into acrylic fabrics, the problem of insufficient antibacterial performance of traditional acrylic fabrics is solved, and significant antibacterial effects and longer-lasting performance are achieved.
Patent Information
- Application Number
- CN202510157289.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-13
AI Technical Summary
Traditional acrylic fabrics are difficult to meet market demand in terms of antibacterial properties, and the existing methods of introducing antibacterial agents have problems with dispersion uniformity and durability.
By introducing modified nanocellulose and silver-carrying carbon spheres, they are dispersed into acrylic fibers, and the dual antibacterial mechanism is achieved by utilizing the high specific surface area and dispersion of nanocellulose and the immobility of silver ions in silver-carrying carbon spheres.
It significantly improves the antibacterial effect of antibacterial acrylic fabric, can effectively inhibit the growth and reproduction of various bacteria, and provides a healthier and safer wearing environment.
Smart Images

Figure CN119800543A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of acrylic fabrics and relates to a preparation process of antibacterial acrylic fabrics. Background Art
[0002] Acrylic, also known as polyacrylonitrile fiber, is a synthetic fiber made from acrylonitrile and other monomers by wet spinning or dry spinning. Its performance is very similar to wool, with excellent elasticity, warmth retention and strength, and outstanding light resistance and chemical resistance. Acrylic fiber is fluffy, curly, soft, and has a 15% higher warmth retention than wool, so it is known as "synthetic wool". In addition, the strength of acrylic is 1 to 2.5 times higher than that of wool, and it has excellent light resistance. Its strength only decreases by 20% after one year of outdoor exposure. It is also resistant to acids, oxidants and general organic solvents, but has poor alkali resistance. These characteristics make acrylic fabrics widely used in many fields such as clothing and home decoration products.
[0003] However, with the increasing demand for textile functionality, especially the requirement for antibacterial properties, traditional acrylic fabrics can no longer meet market demand. Therefore, it is particularly important to develop acrylic fabrics with antibacterial properties.
[0004] In the preparation process of antibacterial acrylic fabrics, the main methods of introducing antibacterial agents include co-spinning, finishing and chemical grafting modification. The co-spinning method is to add antibacterial agents to the acrylic fiber spinning solution, and directly prepare acrylic fibers with antibacterial functions after spinning. This method is simple and easy, but the dispersion uniformity and durability of the antibacterial agent in the fiber are difficult to guarantee. The finishing method is to attach the antibacterial agent to the fiber surface by impregnation, coating, etc. This method is easy to fall off and the antibacterial property is difficult to last. The chemical grafting modification method is to graft the antibacterial agent to the fiber surface or inside through chemical reaction. This method has good and lasting antibacterial properties, but the process is relatively complicated. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a preparation process of an antibacterial acrylic fabric. Through the preparation process provided by the present invention, modified nanocellulose and silver-loaded carbon balls are successfully introduced into acrylic fibers. As a new type of nanomaterial, modified nanocellulose has excellent specific surface area and dispersibility, and can be used as a carrier to effectively load antibacterial components. The silver-loaded carbon balls utilize the broad-spectrum antibacterial properties of silver ions, and fix the silver ions on the surface and inside of the porous carbon balls by physical adsorption and chemical bonding, thereby avoiding the loss of silver ions and achieving the persistence of antibacterial properties. The introduction of this dual antibacterial mechanism makes the prepared antibacterial acrylic fabric have a significant antibacterial effect, can effectively inhibit the growth and reproduction of a variety of bacteria, and provide a healthier and safer wearing environment for the wearer.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The present invention provides a preparation process of an antibacterial acrylic fabric, the preparation process comprising:
[0008] (I) dissolving a polymer monomer in deionized water to obtain a monomer solution, heating the monomer solution, adding ammonium persulfate and sodium bisulfite during the heating process, washing with water, granulating, and drying to obtain a polymer powder after the reaction is completed, and then dissolving the polymer powder in an organic solvent after alkali treatment to obtain an acrylic fiber stock solution;
[0009] (II) mixing, stirring and heating the nanocellulose and N,N'-carbonyldiimidazole solution to react, and obtaining an intermediate product solution after the reaction is completed; adding an octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, and filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;
[0010] (III) dispersing porous carbon spheres in deionized water, mixing uniformly to obtain a carbon sphere dispersion, adding a silver nitrate solution to the carbon sphere dispersion, mixing and stirring uniformly to obtain a precursor solution, adding a sodium citrate solution to the precursor solution, mixing and stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain silver-loaded carbon spheres;
[0011] (IV) dispersing the modified nanocellulose obtained in step (II) and the silver-loaded carbon balls obtained in step (III) in the acrylic fiber stock solution obtained in step (I) to obtain a spinning solution; spraying the spinning solution into a coagulation bath through a spinning head to form primary fibers after coagulation; and the primary fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fiber fabric.
[0012] Through the preparation process provided by the present invention, modified nanocellulose and silver-loaded carbon balls are successfully introduced into acrylic fibers. As a new type of nanomaterial, modified nanocellulose has excellent specific surface area and dispersibility, and can be used as a carrier to effectively load antibacterial components. The silver-loaded carbon balls utilize the broad-spectrum antibacterial properties of silver ions, and fix the silver ions on the surface and inside of the porous carbon balls by physical adsorption and chemical bonding, thereby avoiding the loss of silver ions and achieving the persistence of antibacterial properties. The introduction of this dual antibacterial mechanism makes the prepared antibacterial acrylic fabric have a significant antibacterial effect, can effectively inhibit the growth and reproduction of a variety of bacteria, and provide a healthier and safer wearing environment for the wearer.
[0013] As a natural polymer material, nanocellulose has attracted wide attention due to its excellent mechanical properties and renewability. However, nanocellulose molecules contain a large number of hydroxyl groups and strong intermolecular hydrogen bonds, which makes them prone to agglomeration during the drying process, affecting their dispersion and performance in fabrics. In order to overcome this problem, the present invention uses N,N'-carbonyldiimidazole (CDI) and octadecylamine to hydrophobically modify nanocellulose.
[0014] In the modification process, the nanocellulose and CDI solution are first mixed, stirred and heated to make the imidazole structure on the CDI molecular chain react with the hydroxyl group on the nanocellulose molecular chain to form an ester imidazole structure. This step not only changes the surface properties of the nanocellulose, but also provides active sites for its subsequent reaction with octadecylamine. Then, octadecylamine solution is added to the reaction system, and another imidazole structure on the CDI molecular chain reacts with the amino group on the octadecylamine molecular chain to form a carbamate bond, thereby firmly grafting the octadecylamine molecular chain onto the nanocellulose molecular chain.
[0015] The surface properties of the modified nanocellulose have changed significantly, from hydrophilic to hydrophobic. This change not only improves the uniformity of the dispersion of nanocellulose in the fabric, but also reduces the occurrence of agglomeration. At the same time, the introduction of octadecylamine molecular chains forms a brush-like structure on the surface of nanocellulose, which further enhances the stability of nanocellulose in the fabric and avoids the occurrence of flocculation.
[0016] The uniform dispersion of modified nanocellulose in antibacterial acrylic fabric is the basis for its mechanical reinforcement. Due to the change in the surface properties of nanocellulose, its dispersion in the fabric has been significantly improved. This not only allows nanocellulose to combine more fully with the fabric fibers, but also promotes the formation of a nanocellulose reinforcement network. This network structure can more effectively transmit and disperse stress, thereby improving the overall mechanical properties of the fabric.
[0017] The brush-like structure formed by the octadecylamine molecular chain on the surface of nanocellulose plays an important role in mechanical enhancement. This structure not only increases the contact area and bonding force between nanocellulose and fabric fibers, but also improves the stability of nanocellulose in the fabric. At the same time, the existence of the brush-like structure can also effectively prevent the relative sliding and displacement between fabric fibers, thereby enhancing the tear strength and wear resistance of the fabric.
[0018] The carbamate bonds in modified nanocellulose have excellent chemical stability and good tolerance to acidic and alkaline environments. This feature makes the application of modified nanocellulose in fabrics more extensive and can meet the use requirements in different environments. At the same time, the stability of the carbamate bonds also ensures the long-term performance stability of the modified nanocellulose in the fabric, allowing the mechanical properties of the fabric to continue to be exerted.
[0019] The introduction of modified nanocellulose not only significantly improves the mechanical properties of antibacterial acrylic fabrics, but also has a positive impact on their other properties. For example, due to the uniform dispersion of nanocellulose and the formation of an enhanced network, the wrinkle resistance and drape of the fabric are improved; at the same time, the hydrophobicity of the octadecylamine molecular chain makes the fabric have better waterproof and antifouling properties.
[0020] The present invention loads silver ions or silver nanoparticles on the porous carbon spheres, and the obtained silver-loaded carbon spheres show more significant advantages in antibacterial and antimicrobial properties:
[0021] Broad-spectrum antibacterial properties of silver ions: As a well-known antibacterial element, silver has a strong killing and inhibitory effect on a variety of bacteria, fungi and even viruses. Silver-loaded carbon spheres can quickly and effectively reduce the number of microorganisms in the environment by releasing silver ions, preventing infection and transmission.
[0022] Synergistic effect: The basic antibacterial properties of porous carbon spheres are combined with the broad-spectrum antibacterial properties of silver ions, resulting in a significant synergistic effect. This combination not only broadens the antibacterial spectrum, but also enhances the antibacterial strength, making silver-loaded carbon spheres show higher antibacterial efficiency and wider applicability when facing complex microbial communities.
[0023] Sustained release and long-term antibacterial effect: The three-dimensional porous structure and high specific surface area of porous carbon spheres allow silver ions to be slowly released inside them, avoiding the rapid loss of silver ions and concentration fluctuations, thereby ensuring that the silver-loaded carbon spheres maintain a stable antibacterial effect for a long time. This sustained release characteristic makes silver-loaded carbon spheres particularly suitable for situations where long-term antibacterial protection is required.
[0024] Environmental friendliness and biocompatibility: Although silver ions have antibacterial activity, excessive use may cause environmental pollution and biological toxicity. Porous carbon spheres, as carriers, can accurately control the release of silver ions, reduce unnecessary silver ion leakage, and thus reduce the negative impact on the environment. At the same time, chitosan-based porous carbon spheres themselves have good biocompatibility and will not produce significant toxicity to human cells, ensuring the safety of silver-loaded carbon spheres in medical and health fields.
[0025] Since the antibacterial acrylic fabric prepared by the present invention has excellent antibacterial performance, good comprehensive performance and environmental protection, it can be widely used in multiple fields such as clothing, household goods, medical supplies, etc. In particular, in the medical field, the use of antibacterial fabrics can effectively reduce the risk of cross infection and improve medical quality and safety. In addition, in the field of clothing and household goods, the application of antibacterial fabrics can also meet consumers' needs for health, comfort and environmental protection, and enhance the added value and market competitiveness of products.
[0026] The preparation process of an antibacterial acrylic fabric proposed in the present invention has shown significant beneficial effects in improving antibacterial performance, optimizing preparation process, enhancing comprehensive performance, improving environmental protection and sustainability, and expanding application fields. The innovation and application of this process not only provides new ideas and technical support for the development of functional textiles, but also makes positive contributions to promoting the transformation and upgrading and sustainable development of the textile industry.
[0027] As a preferred technical solution of the present invention, in step (I), the polymer monomers are composed of acrylonitrile, vinyl acetate and sodium propylene sulfonate.
[0028] In some optional examples, the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate is (13-15):1:(0.5-0.6), for example, it can be 13:1:0.5, 13.2:1:0.51, 13.4:1:0.52, 13.6:1:0.53, 13.8:1:0.54, 14:1:0.55, 14.2:1:0.56, 14.4:1:0.57, 14.6:1:0.58, 14.8:1:0.59 or 15:1:0.6, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional examples, the mass fraction of the polymer monomer in the monomer solution is 20-30wt%, for example, it can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the heating temperature of the monomer solution is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the heating time of the monomer solution is 0.5 to 1.5 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the amount of ammonium persulfate added is 0.15-0.18 wt% of the mass of the polymer monomer in the monomer solution, for example, it can be 0.15 wt%, 0.155 wt%, 0.16 wt%, 0.165 wt%, 0.17 wt%, 0.175 wt% or 0.18 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the amount of sodium bisulfite added is 1 to 1.5 wt% of the mass of the polymer monomer in the monomer solution, for example, it can be 1.0 wt%, 1.05 wt%, 1.1 wt%, 1.15 wt%, 1.2 wt%, 1.25 wt%, 1.3 wt%, 1.35 wt%, 1.4 wt%, 1.45 wt% or 1.5 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] As a preferred technical solution of the present invention, in step (I), the alkali treatment operation steps include:
[0035] The polymer powder is dispersed in a sodium hydroxide solution and heated, and then filtered, washed and dried to obtain a modified polymer powder.
[0036] In some optional examples, the sodium hydroxide solution consists of sodium hydroxide and ethanol aqueous solution.
[0037] In some optional examples, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 15-20wt%, for example, it can be 15wt%, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt%, 18wt%, 18.5wt%, 19wt%, 19.5wt% or 20wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the mass fraction of ethanol in the ethanol aqueous solution is 80-90wt%, for example, it can be 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt% or 90wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional instances, the heating temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional examples, the heating time is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the organic solvent is N,N-dimethylacetamide or dimethyl sulfoxide.
[0042] In some optional examples, the mass fraction of the modified polymer powder in the acrylic fiber stock solution is 30-40wt%, for example, it can be 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] As a preferred technical solution of the present invention, in step (II), the N,N'-carbonyldiimidazole solution consists of N,N'-carbonyldiimidazole and dichloromethane.
[0044] In some optional examples, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2-0.3 mol / L, for example, it can be 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the mass ratio of the nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1.3-1.5), for example, it can be 1:1.3, 1:1.32, 1:1.34, 1:1.36, 1:1.38, 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.48 or 1:1.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the mixing and stirring time of the nanocellulose and the N,N'-carbonyldiimidazole solution is 20 to 30 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the temperature for mixing and stirring the nanocellulose and the N,N'-carbonyldiimidazole solution is 35-45°C, for example, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, in step (II), the octadecylamine solution consists of octadecylamine and dichloromethane.
[0049] In some optional examples, the concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L, for example, it can be 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional examples, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1-1.2), for example, it can be 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the mixing and stirring time of the intermediate product solution and the octadecylamine solution is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the mixing and stirring temperature of the intermediate product solution and the octadecylamine solution is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] As a preferred technical solution of the present invention, in step (III), the porous carbon spheres are prepared by the following method:
[0054] Under stirring conditions, chitosan is dissolved in a dilute hydrochloric acid solution to obtain a chitosan solution; the chitosan solution is heated and carbonized, and dialyzed and dried after cooling to obtain a carbon ball powder; the carbon ball powder is mixed and ground with sodium hydroxide, and high-temperature activation is performed in a protective atmosphere to obtain the porous carbon ball.
[0055] The present invention prepares porous carbon balls with a porous structure under hydrothermal conditions through hydrothermal carbonization technology; then, the porous carbon balls are mixed with silver ions, and the rich pore structure on the surface of the porous carbon balls gives them excellent adsorption capacity, so that the silver ions can be adsorbed on the surface of the porous carbon balls; then, sodium citrate is used as a reducing agent, silver nanoparticles are synthesized in situ under secondary hydrothermal conditions, and the silver nanoparticles are firmly adsorbed on the surface of the porous carbon balls, so that silver-loaded carbon balls with high-efficiency and long-lasting antibacterial activity are prepared.
[0056] Chitosan, as a natural polymer, comes from the shell of crustaceans and has certain antibacterial activity. It can inhibit bacterial growth by destroying bacterial cell walls and affecting bacterial cell membrane permeability. Therefore, although most of the original structure of the porous carbon spheres prepared with chitosan as raw material is destroyed during the carbonization process, its residual antibacterial components or functional groups may still have an inhibitory effect on certain microorganisms, giving the porous carbon spheres certain basic antibacterial properties.
[0057] The porous carbon spheres prepared by the present invention have a high specific surface area and a microporous-mesoporous structure, and the specific surface area is as high as 2500-3500m 2 / g, and the pores are evenly distributed, mainly micropores and mesopores, with a pore size range of 1 to 2nm. This structural feature enables porous carbon balls to efficiently adsorb and concentrate microorganisms in the surrounding environment, increase the contact opportunities between microorganisms and loaded antibacterial substances (such as subsequently loaded silver ions), and thus improve antibacterial efficiency.
[0058] The porous carbon spheres prepared by the present invention also have a rich three-dimensional porous structure, which not only increases the specific surface area, but also facilitates the rapid penetration and diffusion of solution and gas molecules, and promotes material transmission. This means that antibacterial substances can reach and act on target microorganisms more quickly, and it is also conducive to the discharge of microbial metabolites, maintaining the cleanliness and high-efficiency antibacterial state of the surface of the porous carbon spheres.
[0059] In addition, during the carbonization process of chitosan, nitrogen elements will be retained in the porous carbon spheres to form natural nitrogen doping. The introduction of nitrogen atoms can change the electronic structure of carbon materials, enhance their adsorption capacity and antibacterial activity for microorganisms, and further improve the antibacterial properties of porous carbon spheres.
[0060] As a preferred technical solution of the present invention, the concentration of the dilute hydrochloric acid solution is 2 to 3 mol / L, for example, it can be 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L or 3.0 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0061] In some optional examples, the concentration of chitosan in the chitosan solution is 2 to 3 g / mL, for example, 2.0 g / mL, 2.1 g / mL, 2.2 g / mL, 2.3 g / mL, 2.4 g / mL, 2.5 g / mL, 2.6 g / mL, 2.7 g / mL, 2.8 g / mL, 2.9 g / mL or 3.0 g / mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional examples, the heating temperature of the heating carbonization is 200-220°C, for example, it can be 200°C, 202°C, 204°C, 206°C, 208°C, 210°C, 212°C, 214°C, 216°C, 218°C or 220°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the heating time for the heating carbonization is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional examples, the mass ratio of the carbon ball powder to sodium hydroxide is 1:(1-2), for example, it can be 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional examples, the mixed grinding time of the carbon ball powder and sodium hydroxide is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional examples, the protective atmosphere is a nitrogen atmosphere.
[0067] In some optional examples, the heating rate of the high temperature activation is 6 to 8°C / min, for example, it can be 6.0°C / min, 6.2°C / min, 6.4°C / min, 6.6°C / min, 6.8°C / min, 7.0°C / min, 7.2°C / min, 7.4°C / min, 7.6°C / min, 7.8°C / min or 8.0°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] In some optional examples, the heating temperature for high-temperature activation is 700-800°C, for example, it can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the heating time for high temperature activation is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] As a preferred technical solution of the present invention, in step (III), the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2 to 3 wt%, for example, it can be 2.0 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt% or 3.0 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In some optional examples, the mass fraction of the silver nitrate solution is 40-50wt%, for example, it can be 40wt%, 41wt%, 42wt%, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt% or 50wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In some optional examples, the volume ratio of the carbon sphere dispersion to the silver nitrate solution is (20-30):1, for example, it can be 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1 or 30:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the mixing and stirring time of the carbon sphere dispersion and the silver nitrate solution is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the concentration of the sodium citrate solution is 0.2-0.3 mol / L, for example, it can be 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In some optional examples, the mass ratio of sodium citrate in the sodium citrate solution to silver nitrate in the precursor solution is (1.2-1.3):1, for example, it can be 1.2:1, 1.21:1, 1.22:1, 1.23:1, 1.24:1, 1.25:1, 1.26:1, 1.27:1, 1.28:1, 1.29:1 or 1.3:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some optional examples, the stirring time when the precursor solution and the sodium citrate solution are mixed is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] In some optional examples, the heating temperature when the precursor solution and the sodium citrate solution are mixed is 100-110°C, for example, it can be 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] As a preferred technical solution of the present invention, in step (IV), the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is (0.01-0.02):(0.1-0.2):1, for example, it can be 0.01:0.1:1, 0.011:0.11:1, 0.012:0.12:1, 0.013:0.13:1, 0.014:0.14:1, 0.015:0.15:1, 0.016:0.16:1, 0.017:0.17:1, 0.018:0.18:1, 0.019:0.19:1 or 0.02:0.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0079] In some optional examples, the temperature of the spinning solution when it is ejected from the spinning head is controlled at 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] In some optional examples, the spinneret diameter of the spinning head is 0.06 to 0.07 mm, for example, it can be 0.06 mm, 0.061 mm, 0.062 mm, 0.063 mm, 0.064 mm, 0.065 mm, 0.066 mm, 0.067 mm, 0.068 mm, 0.069 mm or 0.07 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In some optional examples, the extrusion speed of the spinning head is 0.7 to 0.8 m / min, for example, it can be 0.7 m / min, 0.71 m / min, 0.72 m / min, 0.73 m / min, 0.74 m / min, 0.75 m / min, 0.76 m / min, 0.77 m / min, 0.78 m / min, 0.79 m / min or 0.8 m / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In some optional examples, the coagulation bath is a polyacrylonitrile aqueous solution.
[0083] In some optional instances, the mass fraction of polyacrylonitrile in the coagulation bath is 10 to 15 wt%, for example, it can be 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt% or 15 wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] In some optional embodiments, the temperature of the coagulation bath is 10-20°C, for example, it can be 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In some optional instances, the circulation rate of the coagulation bath is 30,000 to 40,000 kg / h, for example, 30,000 kg / h, 31,000 kg / h, 32,000 kg / h, 33,000 kg / h, 34,000 kg / h, 35,000 kg / h, 36,000 kg / h, 37,000 kg / h, 38,000 kg / h, 39,000 kg / h or 40,000 kg / h, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0086] As a preferred technical solution of the present invention, in step (IV), the stretching is carried out in a stretching machine.
[0087] In some optional examples, the drafting multiple of the drafting machine is 3 to 4, for example, it can be 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9 or 4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] In some optional instances, the stretching speed of the stretching machine is 250-350 m / min, for example, it can be 250 m / min, 260 m / min, 270 m / min, 280 m / min, 290 m / min, 300 m / min, 310 m / min, 320 m / min, 330 m / min, 340 m / min or 350 m / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0089] In some optional examples, the water washing is performed in a water washing tank.
[0090] In some optional instances, the water temperature in the washing tank is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] In some optional examples, the washing time is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0092] In some optional instances, the water circulation rate in the washing tank is 2000-3000 L / h, for example, it can be 2000 L / h, 2100 L / h, 2200 L / h, 2300 L / h, 2400 L / h, 2500 L / h, 2600 L / h, 2700 L / h, 2800 L / h, 2900 L / h or 3000 L / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In some optional examples, the drying temperature is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] In some optional examples, the drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] Compared with the prior art, the present invention has the following beneficial effects:
[0096] Through the preparation process provided by the present invention, modified nanocellulose and silver-loaded carbon balls are successfully introduced into acrylic fibers. As a new type of nanomaterial, modified nanocellulose has excellent specific surface area and dispersibility, and can be used as a carrier to effectively load antibacterial components. The silver-loaded carbon balls utilize the broad-spectrum antibacterial properties of silver ions, and fix the silver ions on the surface and inside of the porous carbon balls by physical adsorption and chemical bonding, thereby avoiding the loss of silver ions and achieving the persistence of antibacterial properties. The introduction of this dual antibacterial mechanism makes the prepared antibacterial acrylic fabric have a significant antibacterial effect, can effectively inhibit the growth and reproduction of a variety of bacteria, and provide a healthier and safer wearing environment for the wearer. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 This is a process flow chart for preparing the antibacterial acrylic fabric provided in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0098] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0099] The chemical reagents used in the specific embodiments of the present invention are all commercially available products, and their specifications, models, manufacturers and other information are as follows:
[0100] Acrylonitrile: purity 99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0101] Vinyl acetate: CG4, purity 99%, purchased from Shandong Zhengxing New Materials Co., Ltd.;
[0102] Sodium propylene sulfonate: industrial grade, purchased from Kangdisi Chemical (Hubei) Co., Ltd.;
[0103] Ammonium persulfate: industrial grade, purchased from Jinan Guocheng Chemical Co., Ltd.;
[0104] Sodium bisulfite: industrial grade, purchased from Jinan Yuanfei Weiye Chemical Co., Ltd.;
[0105] N,N-dimethylacetamide: industrial grade, purchased from Shandong Zhengxing New Materials Co., Ltd.;
[0106] Dimethyl sulfoxide: industrial grade, purchased from Changzhou Huihe Chemical Co., Ltd.;
[0107] Sodium hydroxide: purity 99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0108] Nanocellulose: purity 99%, purchased from Shanghai Jingkang Bioengineering Co., Ltd.;
[0109] N,N'-Carbonyldiimidazole: purity 99%, purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.;
[0110] Octadecanamine: purity 99%, purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd.;
[0111] Dichloromethane: industrial grade, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0112] Chitosan: purity 90%, purchased from Hubei Shiteng Chemical Technology Co., Ltd.;
[0113] Dilute hydrochloric acid: industrial grade, purchased from Tianjin Damao Chemical Reagent Factory;
[0114] Silver nitrate: purity 99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0115] Sodium citrate: purity 99%, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0116] Example 1
[0117] This embodiment provides a preparation process of an antibacterial acrylic fabric, such as Figure 1 As shown, the preparation process specifically includes the following steps:
[0118] (1) dissolving acrylonitrile, vinyl acetate and sodium propylene sulfonate in deionized water to obtain a monomer solution, wherein the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate in the polymer monomer is 13:1:0.5, and the mass fraction of the polymer monomer in the monomer solution is 20wt%; heating the monomer solution at 55° C. for 1.5 hours, and adding ammonium persulfate and sodium bisulfite simultaneously 10 minutes after the start of heating, wherein the amount of ammonium persulfate added is 0.15wt% of the mass of the polymer monomer, and the amount of sodium bisulfite added is 1wt% of the mass of the polymer monomer; after the reaction is completed, washing, granulating and drying to obtain a polymer powder;
[0119] The polymer powder is dispersed in a sodium hydroxide solution, wherein the ratio of the polymer powder to the sodium hydroxide solution is 20 g:1 L, wherein the sodium hydroxide solution is composed of sodium hydroxide and an ethanol aqueous solution, wherein the mass fraction of the sodium hydroxide in the sodium hydroxide solution is 15 wt %, and the mass fraction of the ethanol in the ethanol aqueous solution is 80 wt %; the polymer powder and the sodium hydroxide solution are heated at 80° C. for 2 h, and then filtered, washed with deionized water, and dried to obtain a modified polymer powder; the modified polymer powder is dissolved in N,N-dimethylacetamide to obtain an acrylic fiber stock solution, wherein the mass fraction of the modified polymer powder in the acrylic fiber stock solution is 30 wt %;
[0120] (2) mixing and stirring the nanocellulose and N,N'-carbonyldiimidazole solution, and heating at 35°C for 30 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.3, and after the reaction is completed, an intermediate product solution is obtained;
[0121] Adding an octadecylamine solution to the intermediate product solution, the octadecylamine solution is composed of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.2 mol / L, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1, the intermediate product solution and the octadecylamine solution are mixed and stirred at 55° C. for 5 hours to react, and after the reaction is completed, filtering, washing with deionized water and drying are performed to obtain modified nanocellulose;
[0122] (3) Under stirring conditions, chitosan was dissolved in a dilute hydrochloric acid aqueous solution with a concentration of 2 mol / L to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution was 2 g / mL; the chitosan solution was heated to 200°C and kept warm for 12 h to complete heating carbonization, and then dialyzed and dried after cooling to obtain carbon sphere powder; the carbon sphere powder was mixed and ground with sodium hydroxide in a mass ratio of 1:1 for 20 min, and heated to 700°C at a heating rate of 6°C / min in a nitrogen atmosphere and kept warm for 3 h to complete high-temperature activation to obtain porous carbon spheres;
[0123] The porous carbon spheres are dispersed in deionized water, and the mixture is uniformly mixed to obtain a carbon sphere dispersion, wherein the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2wt%; a silver nitrate aqueous solution with a mass fraction of 40wt% is added to the carbon sphere dispersion, and the volume ratio of the carbon sphere dispersion to the silver nitrate aqueous solution is 20:1; the carbon sphere dispersion and the silver nitrate aqueous solution are mixed and stirred for 2h to obtain a precursor solution; a sodium citrate aqueous solution with a concentration of 0.2mol / L is added to the precursor solution, and the mass ratio of the sodium citrate in the sodium citrate aqueous solution to the silver nitrate in the precursor solution is 1.2:1; the precursor solution and the sodium citrate aqueous solution are mixed and stirred at 100°C for 3h to react, and after the reaction is completed, the mixture is filtered, washed with deionized water and dried to obtain silver-loaded carbon spheres;
[0124] (4) dispersing the modified nanocellulose obtained in step (2) and the silver-loaded carbon spheres obtained in step (3) in the acrylic fiber stock solution obtained in step (1) to obtain a spinning solution, wherein the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is 0.01:0.1:1; spraying the spinning solution into a coagulation bath at a temperature of 10° C. through a spinning head to form primary fibers after coagulation, wherein the temperature of the spinning solution when ejected from the spinning head is controlled at 80° C., the spinneret diameter of the spinning head is 0.06 mm, the extrusion speed of the spinning head is 0.7 m / min, the coagulation bath is a polyacrylonitrile aqueous solution with a mass fraction of 10 wt%, and the circulation rate of the coagulation bath is 30000 kg / h;
[0125] The obtained spun fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fabric, wherein the stretching multiple of the stretching machine is 3, the stretching speed is 250 m / min; the water temperature in the washing tank is 50° C., the washing time is 20 min, and the water circulation volume in the washing tank is 2000 L / h; the drying temperature is 100° C., and the drying time is 24 h.
[0126] Example 2
[0127] This embodiment provides a preparation process of an antibacterial acrylic fabric, such as Figure 1 As shown, the preparation process specifically includes the following steps:
[0128] (1) acrylonitrile, vinyl acetate and sodium propylene sulfonate are dissolved in deionized water to obtain a monomer solution, wherein the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate in the polymer monomer is 13.5:1:0.52, and the mass fraction of the polymer monomer in the monomer solution is 22wt%; the monomer solution is heated at 58° C. for 1.2 hours, and ammonium persulfate and sodium bisulfite are added simultaneously 10 minutes after the start of heating, wherein the amount of ammonium persulfate added is 0.16wt% of the mass of the polymer monomer, and the amount of sodium bisulfite added is 1.2wt% of the mass of the polymer monomer; after the reaction is completed, the polymer powder is washed with water, granulated and dried;
[0129] The polymer powder is dispersed in a sodium hydroxide solution, wherein the ratio of the polymer powder to the sodium hydroxide solution is 20 g:1 L, wherein the sodium hydroxide solution is composed of sodium hydroxide and an ethanol aqueous solution, wherein the mass fraction of the sodium hydroxide in the sodium hydroxide solution is 16 wt %, and the mass fraction of the ethanol in the ethanol aqueous solution is 82 wt %; the polymer powder and the sodium hydroxide solution are heated at 82° C. for 1.8 h, and then filtered, washed with deionized water, and dried to obtain a modified polymer powder; the modified polymer powder is dissolved in N,N-dimethylacetamide to obtain an acrylic fiber stock solution, wherein the mass fraction of the modified polymer powder in the acrylic fiber stock solution is 32 wt %;
[0130] (2) mixing and stirring the nanocellulose and N,N'-carbonyldiimidazole solution, and heating at 38°C for 28 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.22 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.35, and after the reaction is completed, an intermediate product solution is obtained;
[0131] Adding an octadecylamine solution to the intermediate product solution, the octadecylamine solution is composed of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.22 mol / L, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.05, the intermediate product solution and the octadecylamine solution are mixed and stirred at 58°C for 4.5 hours to react, and after the reaction is completed, filtering, washing with deionized water and drying are performed to obtain modified nanocellulose;
[0132] (3) Under stirring conditions, chitosan was dissolved in a dilute hydrochloric acid aqueous solution with a concentration of 2.2 mol / L to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution was 2.2 g / mL; the chitosan solution was heated to 205°C and kept warm for 11.5 h to complete heating carbonization, and then dialyzed and dried after cooling to obtain carbon sphere powder; the carbon sphere powder was mixed and ground with sodium hydroxide at a mass ratio of 1:1.2 for 22 min, and heated to 720°C at a heating rate of 6.5°C / min in a nitrogen atmosphere and kept warm for 2.8 h to complete high-temperature activation to obtain porous carbon spheres;
[0133] The porous carbon spheres are dispersed in deionized water, and the mixture is uniformly mixed to obtain a carbon sphere dispersion, wherein the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2.2 wt %; a silver nitrate aqueous solution with a mass fraction of 42 wt % is added to the carbon sphere dispersion, and the volume ratio of the carbon sphere dispersion to the silver nitrate aqueous solution is 22:1; the carbon sphere dispersion and the silver nitrate aqueous solution are mixed and stirred for 2.2 h to obtain a precursor solution; a sodium citrate aqueous solution with a concentration of 0.22 mol / L is added to the precursor solution, and the mass ratio of the sodium citrate in the sodium citrate aqueous solution to the silver nitrate in the precursor solution is 1.22:1; the precursor solution and the sodium citrate aqueous solution are mixed and stirred at 102° C. for 2.8 h to react, and after the reaction is completed, the mixture is filtered, washed with deionized water, and dried to obtain silver-loaded carbon spheres;
[0134] (4) dispersing the modified nanocellulose obtained in step (2) and the silver-loaded carbon spheres obtained in step (3) in the acrylic fiber stock solution obtained in step (1) to obtain a spinning solution, wherein the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is 0.012:0.12:1; spraying the spinning solution into a coagulation bath at a temperature of 12° C. through a spinning head to form primary fibers after coagulation, wherein the temperature of the spinning solution when ejected from the spinning head is controlled at 82° C., the spinneret diameter of the spinning head is 0.062 mm, the extrusion speed of the spinning head is 0.72 m / min, the coagulation bath is a polyacrylonitrile aqueous solution with a mass fraction of 12 wt%, and the circulation rate of the coagulation bath is 32000 kg / h;
[0135] The obtained spun fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fabric, wherein the stretching multiple of the stretching machine is 3.2, the stretching speed is 280 m / min; the water temperature in the washing tank is 52° C., the washing time is 18 min, the water circulation volume in the washing tank is 2200 L / h; the drying temperature is 105° C., and the drying time is 21 h.
[0136] Example 3
[0137] This embodiment provides a preparation process of an antibacterial acrylic fabric, such as Figure 1 As shown, the preparation process specifically includes the following steps:
[0138] (1) dissolving acrylonitrile, vinyl acetate and sodium propylene sulfonate in deionized water to obtain a monomer solution, wherein the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate in the polymer monomer is 14:1:0.55, and the mass fraction of the polymer monomer in the monomer solution is 25wt%; heating the monomer solution at 60° C. for 1 hour, and adding ammonium persulfate and sodium bisulfite simultaneously 10 minutes after the start of heating, wherein the amount of ammonium persulfate added is 0.17wt% of the mass of the polymer monomer, and the amount of sodium bisulfite added is 1.3wt% of the mass of the polymer monomer; after the reaction is completed, washing, granulating and drying to obtain a polymer powder;
[0139] The polymer powder is dispersed in a sodium hydroxide solution, wherein the ratio of the polymer powder to the sodium hydroxide solution is 20 g:1 L, wherein the sodium hydroxide solution is composed of sodium hydroxide and an ethanol aqueous solution, wherein the mass fraction of the sodium hydroxide in the sodium hydroxide solution is 17 wt %, and the mass fraction of the ethanol in the ethanol aqueous solution is 85 wt %; the polymer powder and the sodium hydroxide solution are heated at 85° C. for 1.5 h, and then filtered, washed with deionized water, and dried to obtain a modified polymer powder; the modified polymer powder is dissolved in N,N-dimethylacetamide to obtain an acrylic fiber stock solution, wherein the mass fraction of the modified polymer powder in the acrylic fiber stock solution is 35 wt %;
[0140] (2) mixing and stirring the nanocellulose and N,N'-carbonyldiimidazole solution, and heating at 40°C for 25 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.25 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.4, and after the reaction is completed, an intermediate product solution is obtained;
[0141] Adding an octadecylamine solution to the intermediate product solution, the octadecylamine solution is composed of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.25 mol / L, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.1, the intermediate product solution and the octadecylamine solution are mixed and stirred at 60°C for 4 hours to react, and after the reaction is completed, filtering, washing with deionized water and drying are performed to obtain modified nanocellulose;
[0142] (3) Under stirring conditions, chitosan was dissolved in a 2.5 mol / L dilute hydrochloric acid aqueous solution to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution was 2.5 g / mL; the chitosan solution was heated to 210°C and kept warm for 11 h to complete heating carbonization, and then dialyzed and dried after cooling to obtain carbon sphere powder; the carbon sphere powder was mixed and ground with sodium hydroxide at a mass ratio of 1:1.5 for 25 min, and heated to 750°C at a heating rate of 7°C / min in a nitrogen atmosphere and kept warm for 2.5 h to complete high-temperature activation to obtain porous carbon spheres;
[0143] The porous carbon spheres are dispersed in deionized water, and the mixture is uniformly mixed to obtain a carbon sphere dispersion, wherein the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2.5wt%; a silver nitrate aqueous solution with a mass fraction of 45wt% is added to the carbon sphere dispersion, and the volume ratio of the carbon sphere dispersion to the silver nitrate aqueous solution is 25:1; the carbon sphere dispersion and the silver nitrate aqueous solution are mixed and stirred for 2.5h to obtain a precursor solution; a sodium citrate aqueous solution with a concentration of 0.25mol / L is added to the precursor solution, and the mass ratio of the sodium citrate in the sodium citrate aqueous solution to the silver nitrate in the precursor solution is 1.25:1; the precursor solution and the sodium citrate aqueous solution are mixed and stirred at 105°C for 2.5h to react, and after the reaction is completed, the mixture is filtered, washed with deionized water and dried to obtain silver-loaded carbon spheres;
[0144] (4) dispersing the modified nanocellulose obtained in step (2) and the silver-loaded carbon spheres obtained in step (3) in the acrylic fiber stock solution obtained in step (1) to obtain a spinning solution, wherein the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is 0.015:0.15:1; spraying the spinning solution into a coagulation bath at a temperature of 15° C. through a spinning head to form primary fibers after coagulation, wherein the temperature of the spinning solution when ejected from the spinning head is controlled at 85° C., the spinneret diameter of the spinning head is 0.065 mm, the extrusion speed of the spinning head is 0.75 m / min, the coagulation bath is a polyacrylonitrile aqueous solution with a mass fraction of 13 wt%, and the circulation rate of the coagulation bath is 35000 kg / h;
[0145] The obtained spun fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fabric, wherein the stretching multiple of the stretching machine is 3.5, the stretching speed is 300 m / min; the water temperature in the washing tank is 55° C., the washing time is 15 min, the water circulation volume in the washing tank is 2500 L / h; the drying temperature is 110° C., and the drying time is 18 h.
[0146] Example 4
[0147] This embodiment provides a preparation process of an antibacterial acrylic fabric, such as Figure 1 As shown, the preparation process specifically includes the following steps:
[0148] (1) acrylonitrile, vinyl acetate and sodium propylene sulfonate are dissolved in deionized water to obtain a monomer solution, wherein the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate in the polymer monomer is 14.5:1:0.58, and the mass fraction of the polymer monomer in the monomer solution is 28wt%; the monomer solution is heated at 62°C for 0.8h, and ammonium persulfate and sodium bisulfite are added simultaneously 10min after the start of heating, wherein the amount of ammonium persulfate added is 0.17wt% of the mass of the polymer monomer, and the amount of sodium bisulfite added is 1.4wt% of the mass of the polymer monomer; after the reaction is completed, the polymer powder is washed with water, granulated and dried;
[0149] The polymer powder is dispersed in a sodium hydroxide solution, wherein the ratio of the polymer powder to the sodium hydroxide solution is 20 g:1 L, wherein the sodium hydroxide solution is composed of sodium hydroxide and an ethanol aqueous solution, wherein the mass fraction of the sodium hydroxide in the sodium hydroxide solution is 18 wt %, and the mass fraction of the ethanol in the ethanol aqueous solution is 88 wt %; the polymer powder and the sodium hydroxide solution are heated at 88° C. for 1.2 h, and then filtered, washed with deionized water, and dried to obtain a modified polymer powder; the modified polymer powder is dissolved in dimethyl sulfoxide to obtain an acrylic stock solution, wherein the mass fraction of the modified polymer powder in the acrylic stock solution is 38 wt %;
[0150] (2) mixing and stirring the nanocellulose and N,N'-carbonyldiimidazole solution, and heating at 42° C. for 22 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.28 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.45, and after the reaction is completed, an intermediate product solution is obtained;
[0151] Adding an octadecylamine solution to the intermediate product solution, the octadecylamine solution is composed of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.28 mol / L, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.15, the intermediate product solution and the octadecylamine solution are mixed and stirred at 62°C for 3.5 hours to react, and after the reaction is completed, filtering, washing with deionized water and drying are performed to obtain modified nanocellulose;
[0152] (3) Under stirring conditions, chitosan was dissolved in a dilute hydrochloric acid aqueous solution with a concentration of 2.8 mol / L to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution was 2.8 g / mL; the chitosan solution was heated to 215°C and kept warm for 10.5 h to complete heating carbonization, and then dialyzed and dried after cooling to obtain carbon sphere powder; the carbon sphere powder was mixed and ground with sodium hydroxide at a mass ratio of 1:1.8 for 28 min, and heated to 780°C at a heating rate of 7.5°C / min in a nitrogen atmosphere and kept warm for 2.2 h to complete high-temperature activation to obtain porous carbon spheres;
[0153] The porous carbon spheres are dispersed in deionized water, and the mixture is uniformly mixed to obtain a carbon sphere dispersion, wherein the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2.8 wt %; a silver nitrate aqueous solution with a mass fraction of 48 wt % is added to the carbon sphere dispersion, and the volume ratio of the carbon sphere dispersion to the silver nitrate aqueous solution is 28:1; the carbon sphere dispersion and the silver nitrate aqueous solution are mixed and stirred for 2.8 h to obtain a precursor solution; a sodium citrate aqueous solution with a concentration of 0.28 mol / L is added to the precursor solution, and the mass ratio of the sodium citrate in the sodium citrate aqueous solution to the silver nitrate in the precursor solution is 1.28:1; the precursor solution and the sodium citrate aqueous solution are mixed and stirred at 108° C. for 2.2 h to react, and after the reaction is completed, the mixture is filtered, washed with deionized water, and dried to obtain silver-loaded carbon spheres;
[0154] (4) dispersing the modified nanocellulose obtained in step (2) and the silver-loaded carbon spheres obtained in step (3) in the acrylic fiber stock solution obtained in step (1) to obtain a spinning solution, wherein the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is 0.018:0.18:1; spraying the spinning solution into a coagulation bath at a temperature of 18° C. through a spinning head to form primary fibers after coagulation, wherein the temperature of the spinning solution when ejected from the spinning head is controlled at 88° C., the spinneret diameter of the spinning head is 0.068 mm, the extrusion speed of the spinning head is 0.78 m / min, the coagulation bath is a polyacrylonitrile aqueous solution with a mass fraction of 14 wt%, and the circulation rate of the coagulation bath is 38000 kg / h;
[0155] The obtained spun fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fabric, wherein the stretching multiple of the stretching machine is 3.8, the stretching speed is 320 m / min; the water temperature in the washing tank is 58° C., the washing time is 12 min, the water circulation volume in the washing tank is 2800 L / h; the drying temperature is 115° C., and the drying time is 15 h.
[0156] Example 5
[0157] This embodiment provides a preparation process of an antibacterial acrylic fabric, such as Figure 1 As shown, the preparation process specifically includes the following steps:
[0158] (1) dissolving acrylonitrile, vinyl acetate and sodium propylene sulfonate in deionized water to obtain a monomer solution, wherein the mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate in the polymer monomer is 15:1:0.6, and the mass fraction of the polymer monomer in the monomer solution is 30wt%; heating the monomer solution at 65° C. for 0.5 h, and adding ammonium persulfate and sodium bisulfite simultaneously 10 minutes after the start of heating, wherein the amount of ammonium persulfate added is 0.18wt% of the mass of the polymer monomer, and the amount of sodium bisulfite added is 1.5wt% of the mass of the polymer monomer; after the reaction is completed, washing, granulating and drying to obtain a polymer powder;
[0159] The polymer powder is dispersed in a sodium hydroxide solution, wherein the ratio of the polymer powder to the sodium hydroxide solution is 20 g:1 L, wherein the sodium hydroxide solution is composed of sodium hydroxide and an ethanol aqueous solution, wherein the mass fraction of the sodium hydroxide in the sodium hydroxide solution is 20 wt %, and the mass fraction of the ethanol in the ethanol aqueous solution is 90 wt %; the polymer powder and the sodium hydroxide solution are heated at 90° C. for 1 h, and then filtered, washed with deionized water, and dried to obtain a modified polymer powder; the modified polymer powder is dissolved in dimethyl sulfoxide to obtain an acrylic fiber stock solution, wherein the mass fraction of the modified polymer powder in the acrylic fiber stock solution is 40 wt %;
[0160] (2) mixing and stirring the nanocellulose and N,N'-carbonyldiimidazole solution, and heating at 45°C for 20 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.3 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.5, and after the reaction is completed, an intermediate product solution is obtained;
[0161] Adding an octadecylamine solution to the intermediate product solution, the octadecylamine solution is composed of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.3 mol / L, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.2, the intermediate product solution and the octadecylamine solution are mixed and stirred at 65°C for 3 hours to react, and after the reaction is completed, filtering, washing with deionized water and drying are performed to obtain modified nanocellulose;
[0162] (3) Under stirring conditions, chitosan was dissolved in a 3 mol / L dilute hydrochloric acid aqueous solution to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution was 3 g / mL; the chitosan solution was heated to 220°C and kept warm for 10 h to complete heating carbonization, and then dialyzed and dried after cooling to obtain carbon sphere powder; the carbon sphere powder was mixed and ground with sodium hydroxide in a mass ratio of 1:2 for 30 min, and heated to 800°C at a heating rate of 8°C / min in a nitrogen atmosphere and kept warm for 2 h to complete high-temperature activation to obtain porous carbon spheres;
[0163] The porous carbon spheres are dispersed in deionized water, and the mixture is uniformly mixed to obtain a carbon sphere dispersion, wherein the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 3wt%; a silver nitrate aqueous solution with a mass fraction of 50wt% is added to the carbon sphere dispersion, and the volume ratio of the carbon sphere dispersion to the silver nitrate aqueous solution is 30:1; the carbon sphere dispersion and the silver nitrate aqueous solution are mixed and stirred for 3h to obtain a precursor solution; a sodium citrate aqueous solution with a concentration of 0.3mol / L is added to the precursor solution, and the mass ratio of the sodium citrate in the sodium citrate aqueous solution to the silver nitrate in the precursor solution is 1.3:1; the precursor solution and the sodium citrate aqueous solution are mixed and stirred at 110°C for 2h to react, and after the reaction is completed, the mixture is filtered, washed with deionized water and dried to obtain silver-loaded carbon spheres;
[0164] (4) dispersing the modified nanocellulose obtained in step (2) and the silver-loaded carbon spheres obtained in step (3) in the acrylic fiber stock solution obtained in step (1) to obtain a spinning solution, wherein the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is 0.02:0.2:1; spraying the spinning solution into a coagulation bath at a temperature of 20° C. through a spinning head to form primary fibers after coagulation, wherein the temperature of the spinning solution when ejected from the spinning head is controlled at 90° C., the spinneret diameter of the spinning head is 0.07 mm, the extrusion speed of the spinning head is 0.8 m / min, the coagulation bath is a polyacrylonitrile aqueous solution with a mass fraction of 15 wt%, and the circulation rate of the coagulation bath is 40000 kg / h;
[0165] The obtained spun fibers are subjected to stretching, washing, oiling, drying and weaving to obtain the antibacterial acrylic fabric, wherein the stretching multiple of the stretching machine is 4, the stretching speed is 350 m / min; the water temperature in the washing tank is 60° C., the washing time is 10 min, the water circulation volume in the washing tank is 3000 L / h; the drying temperature is 120° C., and the drying time is 12 h.
[0166] Comparative Example 1
[0167] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (2), the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is adjusted to 1:1.2, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0168] Comparative Example 2
[0169] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (2), the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is adjusted to 1:1.6, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0170] Comparative Example 3
[0171] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (2), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:0.8, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0172] Comparative Example 4
[0173] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (2), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:1.5, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0174] Comparative Example 5
[0175] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (3), the volume ratio of the carbon ball dispersion to the silver nitrate aqueous solution is adjusted to 15:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0176] Comparative Example 6
[0177] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (3), the volume ratio of the carbon ball dispersion to the silver nitrate aqueous solution is adjusted to 35:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0178] Comparative Example 7
[0179] This comparative example provides a preparation process of an antibacterial acrylic fabric, which differs from Example 1 in that, in step (4), the mass ratio of modified nanocellulose, silver-loaded carbon balls and acrylic stock solution is adjusted to 0.01:0.08:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0180] Comparative Example 8
[0181] This comparative example provides a preparation process for an antibacterial acrylic fabric, which differs from Example 1 in that, in step (4), the mass ratio of modified nanocellulose, silver-loaded carbon balls and acrylic stock solution is adjusted to 0.01:0.22:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0182] The tensile strength and elongation at break of acrylic fibers were tested using a single fiber universal tester. The tensile rate was 10 mm / min, the clamp distance was 20 mm, and each group of samples was tested 10 times to obtain the average value. The test results of tensile strength and elongation at break are shown in Table 1.
[0183] The antibacterial acrylic fabric prepared in Example 1 was subjected to an Escherichia coli antibacterial test, and the specific test steps are as follows:
[0184] (1) Weigh 1 g of tryptone, 1 g of sodium chloride, and 0.5 g of agar yeast extract powder, add them to a 100-mL volumetric flask, dilute them to 100 mL with deionized water, disperse them by ultrasonication, adjust the pH value of the mixture to 7.2-7.4 with 4 M sodium hydroxide to obtain a liquid culture medium, and sterilize the liquid culture medium at 120° C. and 0.1 MPa for later use;
[0185] (2) Weigh 2.5 g of tryptone, 2.5 g of sodium chloride, and 5 g of agar, add them to a 250 mL volumetric flask, dilute them to 250 mL with deionized water, disperse them by ultrasonication, adjust the pH value of the mixture to 7.2-7.4 with 4 M sodium hydroxide to obtain a solid culture medium, and sterilize the solid culture medium at 120° C. and 0.1 MPa for later use;
[0186] (3) Use a sterilized inoculation loop to pick up Escherichia coli strains, draw three lines on the solid culture medium, and then culture it in a constant temperature incubator at 37°C for 24 hours. Pick a single colony from the cultured solid culture medium and place it in a liquid culture medium. Culture it in a constant temperature oscillator at 37°C for 12-18 hours to obtain a bacterial suspension; take 5 mL of the bacterial suspension and place it in a centrifuge, centrifuge it at 4000 rpm for 20 minutes, wash it twice with PBS (pH = 7.0), and obtain a concentration of 10 9 cfu / mL of bacterial solution;
[0187] (4) Dilute the bacterial solution step by step with PBS to a final dilution concentration of 10 4cfu / mL, 5 mg of the spinning solution prepared in Example 1 was weighed and placed in a centrifuge tube, 4.5 mL of PBS was added for ultrasonic dispersion, and then 0.5 mL of 10 4 cfu / mL of bacterial solution, shake it thoroughly, take 100 μL to coat the plate, place the plate in a 37°C constant temperature incubator for 24 hours, and observe the growth of Escherichia coli colonies.
[0188] The number of Escherichia coli colonies was counted and the antibacterial rate against Escherichia coli was calculated. The test results are shown in Table 1.
[0189] The antibacterial test process of Staphylococcus aureus refers to the antibacterial test process of Escherichia coli mentioned above, and the results are shown in Table 1.
[0190] The colony numbers of Staphylococcus aureus were counted and the antibacterial rate against Staphylococcus aureus was calculated. The test results are shown in Table 1.
[0191] Table 1: Test results
[0192]
[0193]
[0194] It can be seen from the data in Table 1 that the antibacterial acrylic fabric prepared in the embodiment of the present invention has excellent mechanical properties and antibacterial properties.
[0195] It can be seen from the test results of Example 1, Comparative Example 1 and Comparative Example 2 that when the dosage of N,N'-carbonyldiimidazole is too high or too low, it will affect the modification effect on nanocellulose, and further affect the mechanical properties of the antibacterial acrylic fabric.
[0196] It can be seen from the test results of Example 1, Comparative Example 3 and Comparative Example 4 that when the dosage of octadecylamine is too high or too low, it will affect the modification effect on nanocellulose, and further affect the mechanical properties of the antibacterial acrylic fabric.
[0197] It can be seen from the test results of Example 1, Comparative Example 5 and Comparative Example 6 that when the dosage of the silver nitrate solution is too high or too low, it will affect the loading amount of silver nanoparticles in the silver-loaded carbon spheres, thereby affecting the antibacterial properties of the antibacterial acrylic fabric.
[0198] It can be seen from the test results of Example 1, Comparative Example 7 and Comparative Example 8 that when the dosage of silver-loaded carbon balls is too high, the silver-loaded carbon balls are easy to agglomerate, thereby affecting the mechanical properties of the antibacterial acrylic fabric; when the dosage of silver-loaded carbon balls is too low, the antibacterial effect of silver nanoparticles cannot be fully exerted, thereby affecting the antibacterial properties of the antibacterial acrylic fabric.
[0199] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A preparation process of an antibacterial acrylic fabric, characterized in that: The preparation process comprises: (I) dissolving a polymer monomer in deionized water to obtain a monomer solution, heating the monomer solution, adding ammonium persulfate and sodium bisulfite during the heating process, washing with water, granulating, and drying to obtain a polymer powder after the reaction is completed, and then dissolving the polymer powder in an organic solvent after alkali treatment to obtain an acrylic fiber stock solution; (II) mixing, stirring and heating the nanocellulose and N,N'-carbonyldiimidazole solution to react, and obtaining an intermediate product solution after the reaction is completed; adding an octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, and filtering, washing and drying after the reaction is completed to obtain modified nanocellulose; (III) dispersing porous carbon spheres in deionized water, mixing uniformly to obtain a carbon sphere dispersion, adding a silver nitrate solution to the carbon sphere dispersion, mixing and stirring uniformly to obtain a precursor solution, adding a sodium citrate solution to the precursor solution, mixing and stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain silver-loaded carbon spheres; (IV) dispersing the modified nanocellulose obtained in step (II) and the silver-loaded carbon balls obtained in step (III) in the acrylic fiber stock solution obtained in step (I) to obtain a spinning solution; spraying the spinning solution into a coagulation bath through a spinning head to form primary fibers after coagulation; and the primary fibers are stretched, washed, oiled, dried and woven to obtain the antibacterial acrylic fiber fabric.
2. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (I), the polymer monomers are composed of acrylonitrile, vinyl acetate and sodium propylene sulfonate; The mass ratio of acrylonitrile, vinyl acetate and sodium propylene sulfonate is (13-15):1:(0.5-0.6); The mass fraction of the polymer monomer in the monomer solution is 20 to 30 wt %; The heating temperature of the monomer solution is 55-65°C; The heating time of the monomer solution is 0.5 to 1.5 hours; The amount of ammonium persulfate added is 0.15-0.18 wt% of the mass of the polymer monomer in the monomer solution; The amount of sodium bisulfite added is 1 to 1.5 wt % of the mass of the polymer monomer in the monomer solution.
3. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (I), the alkali treatment comprises: Dispersing the polymer powder in a sodium hydroxide solution and heating it, followed by filtering, washing and drying to obtain a modified polymer powder; The sodium hydroxide solution consists of sodium hydroxide and ethanol aqueous solution; The mass fraction of sodium hydroxide in the sodium hydroxide solution is 15-20wt%; The mass fraction of ethanol in the ethanol aqueous solution is 80-90wt%; The heating temperature is 80-90°C; The heating time is 1 to 2 hours; The organic solvent is N,N-dimethylacetamide or dimethyl sulfoxide; The mass fraction of the modified polymer powder in the acrylic fiber stock solution is 30-40wt%.
4. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (II), the N,N'-carbonyldiimidazole solution consists of N,N'-carbonyldiimidazole and dichloromethane; The concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2-0.3 mol / L; The mass ratio of the nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1.3-1.5); The mixing and stirring time of the nanocellulose and the N,N'-carbonyldiimidazole solution is 20 to 30 hours; The temperature for mixing and stirring the nanocellulose and the N,N'-carbonyldiimidazole solution is 35-45°C.
5. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (II), the octadecylamine solution is composed of octadecylamine and dichloromethane; The concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L; The molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1-1.2); The mixing and stirring time of the intermediate product solution and the octadecylamine solution is 3 to 5 hours; The temperature of mixing and stirring the intermediate product solution and the octadecylamine solution is 55-65°C.
6. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (III), the porous carbon spheres are prepared by the following method: Under stirring conditions, chitosan is dissolved in a dilute hydrochloric acid solution to obtain a chitosan solution; the chitosan solution is heated and carbonized, and dialyzed and dried after cooling to obtain a carbon ball powder; the carbon ball powder is mixed and ground with sodium hydroxide, and high-temperature activation is performed in a protective atmosphere to obtain the porous carbon ball.
7. The preparation process of the antibacterial acrylic fabric according to claim 6, characterized in that: The concentration of the dilute hydrochloric acid solution is 2-3 mol / L; The concentration of chitosan in the chitosan solution is 2 to 3 g / mL; The heating temperature of the heating carbonization is 200-220°C; The heating time of the heating carbonization is 10 to 12 hours; The mass ratio of the carbon ball powder to sodium hydroxide is 1:(1-2); The mixing and grinding time of the carbon ball powder and sodium hydroxide is 20 to 30 minutes; The protective atmosphere is a nitrogen atmosphere; The heating rate of the high temperature activation is 6-8°C / min; The heating temperature of the high temperature activation is 700-800°C; The heating time of the high temperature activation is 2 to 3 hours.
8. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (III), the mass fraction of the porous carbon spheres in the carbon sphere dispersion is 2 to 3 wt%; The mass fraction of the silver nitrate solution is 40-50wt%; The volume ratio of the carbon sphere dispersion to the silver nitrate solution is (20-30):1; The mixing and stirring time of the carbon sphere dispersion and the silver nitrate solution is 2 to 3 hours; The concentration of the sodium citrate solution is 0.2-0.3 mol / L; The mass ratio of the sodium citrate in the sodium citrate solution to the silver nitrate in the precursor solution is (1.2-1.3):1; The stirring time when the precursor solution and the sodium citrate solution are mixed is 2 to 3 hours; The heating temperature when the precursor solution and the sodium citrate solution are mixed is 100-110°C.
9. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (IV), the mass ratio of the modified nanocellulose, the silver-loaded carbon spheres and the acrylic fiber stock solution is (0.01-0.02):(0.1-0.2):1; The temperature of the spinning solution when it is ejected from the spinning head is controlled at 80-90°C; The spinneret diameter of the spinning head is 0.06-0.07 mm; The extrusion speed of the spinning head is 0.7-0.8 m / min; The coagulation bath is a polyacrylonitrile aqueous solution; The mass fraction of polyacrylonitrile in the coagulation bath is 10-15wt%; The temperature of the coagulation bath is 10-20°C; The circulation rate of the coagulation bath is 30000-40000 kg / h.
10. The preparation process of the antibacterial acrylic fabric according to claim 1, characterized in that: In step (IV), the drawing is carried out in a drawing machine; The drafting multiple of the drafting machine is 3 to 4; The drafting speed of the drafting machine is 250-350 m / min; The water washing is carried out in a water washing tank; The water temperature in the washing tank is 50-60°C; The washing time is 10 to 20 minutes; The water circulation rate in the washing tank is 2000-3000L / h; The drying temperature is 100-120°C; The drying time is 12 to 24 hours.
Citation Information
Patent Citations
Preparation method of antibacterial polyacrylonitrile fiber
CN110592713A
Preparation method of spherical activated carbon breathable biochemical protective fabric with strong adsorption performance and antibacterial performance
CN114481647A
Far infrared negative ion antibacterial acrylic fabric and preparation method thereof
CN117845358A
Bio-based full-degradable composite film as well as preparation method and application thereof
CN118271809A
Acetic nitrile fibre and preparation method therefor
WO2016127833A1